2012
DOI: 10.1111/j.2042-3306.2012.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

African horse sickness in naturally infected, immunised horses

Abstract: SummaryTo determine whether subclinical cases, together with clinical cases, of African horse sickness (AHS) occur in immunised horses in field conditions, whole blood samples were collected and rectal temperatures recorded weekly from 50 Nooitgedacht ponies resident in open camps at the Faculty of Veterinary Science, University of Pretoria, Onderstepoort, during 2008-2010. The samples were tested for the presence of African horse sickness virus (AHSV) RNA by a recently developed real-time RT-PCR. It was shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 6 publications
2
25
0
1
Order By: Relevance
“…Similarly, changes in the AHS case definition that only came into effect in 2008 (after the 2004 Stellenbosch outbreak) probably resulted in an underestimation of subclinical AHSV infections during that outbreak. Whereas during the Stellenbosch 2004 outbreak only clinically affected, deceased horses were classified as having confirmed cases ( 13 ), major advances in AHS diagnostic testing (e.g., rRT-PCR–based methods) have occurred during the past 10 years that likely substantially increased the detection of subclinical infections by the time of the 2014 outbreaks ( 15 , 32 ). …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, changes in the AHS case definition that only came into effect in 2008 (after the 2004 Stellenbosch outbreak) probably resulted in an underestimation of subclinical AHSV infections during that outbreak. Whereas during the Stellenbosch 2004 outbreak only clinically affected, deceased horses were classified as having confirmed cases ( 13 ), major advances in AHS diagnostic testing (e.g., rRT-PCR–based methods) have occurred during the past 10 years that likely substantially increased the detection of subclinical infections by the time of the 2014 outbreaks ( 15 , 32 ). …”
Section: Resultsmentioning
confidence: 99%
“…However, the simultaneous administration of multiple vaccine strains can result in interference during vaccine virus replication, possibly resulting in incomplete immunity [51,52]. For example, a recent study has shown that immunized horses in an AHS endemic area were infected with AHSV over a 2 year period [53]. Our results suggest that incomplete immunity with a reduction in the mortality rate of the horses might lead to an increase in the basic reproduction number (figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent study showed that horses immunized against AHSV can be infected both clinically and subclinically with AHSV following natural infection in field conditions. Indeed, the level of viraemia observed in subclinically infected horses might be sufficient to infect midges with AHSV [10]. These attenuated vaccines have other disadvantages, such as the possible exchange of genome segments with field strains and the impossibility to distinguish (naturally) infected and vaccinated animals (‘DIVA’),…”
Section: Introductionmentioning
confidence: 99%